Composite oil-based separator, its manufacturing method, and secondary battery

The composite oil-based separator with a moisturizing coating addresses the issue of static electricity in lithium-ion battery separators, enhancing liquid absorption and retention, and enabling rapid charging performance by forming a layer structure with water vapor on the substrate film.

JP2025508143AActive Publication Date: 2025-03-21HUIZHOU LIWINON ELECTRONIC TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024554186
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-21
Filing Date
2023-03-20
Publication Date
2025-03-21
Estimated Expiration
2043-03-20

AI Technical Summary

Technical Problem

Existing oil-based separators for lithium-ion batteries suffer from high static electricity generation, leading to wrinkles during electrode assembly winding and low pass rates, which hinder fast charging performance.

Method used

A composite oil-based separator with a moisturizing coating comprising an inorganic filler, an adhesive polymer, and a moisturizing polymer is applied to the substrate film, forming a layer structure with water vapor to reduce static electricity and improve liquid absorption and retention.

Benefits of technology

The composite separator achieves reduced static electricity, improved liquid absorption and retention, high lithium ion conductivity, and enhanced hardness of the electrode assembly, enabling rapid charging at rates of 3C or higher while minimizing defects during assembly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025508143000001_ABST
    Figure 2025508143000001_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of separators, and in particular to a composite oil-based separator and a manufacturing method thereof. The composite oil-based separator includes a base film and a moisture-retaining coating applied to at least one side of the base film, the moisture-retaining coating including an inorganic filler, an adhesive polymer, and a moisture-retaining polymer. In the composite oil-based separator of the present invention, the moisture-retaining coating is provided to form a layer structure having water vapor on the surface of the base film, thereby reducing the static electricity strength of the composite oil-based separator and preventing wrinkles when the separator is used in an electrode assembly and wound up.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a composite oil-based separator and a manufacturing method thereof, and a secondary battery. [Background technology]

[0002] Lithium-ion batteries have the characteristics of high operating voltage, high energy density, long cycle life, no memory effect, and no pollution, and are the main energy source for various electronic products. They are also environmentally friendly and non-polluting secondary batteries. In addition, lithium-ion batteries are in line with the trend of the development of energy and environmental protection in the world today, and therefore the use of lithium-ion batteries in various industries is rapidly increasing. As a result, the safety, capacity, and fast charging performance of lithium-ion batteries are attracting more and more attention, and fast charging in particular is an urgent need.

[0003] The main materials of lithium-ion batteries are positive electrode material, negative electrode material, electrolyte, and separator. The main function of the separator is to achieve the rapid movement of lithium ions between the positive and negative electrodes during charging and discharging by isolating the positive and negative electrodes, preventing the passage of electrons, and allowing the passage of ions. Based on the safety and capacity of lithium-ion batteries, the liquid absorption and liquid retention of the separator have become the focus of research in order to improve the fast charging performance of the electrode assembly. At present, efforts are being made to improve the liquid absorption and liquid retention of the separator by applying a water-based polymer coating or an oil-based polymer coating to the separator. However, water-based separators can currently only achieve a fast charging speed of 3C or less, and oil-based separators are used for speeds higher than that. However, oil-based separators have the problem of being prone to static electricity, which has a significant impact on the winding of the electrode assembly and results in a low pass rate for the electrode assembly. Summary of the Invention

[0004] The first objective of the present invention is to provide a composite oil-based separator that can reduce the static electricity strength of the composite oil-based separator by forming a layer structure with water vapor on the surface of the base film, and can prevent wrinkles when the separator is used in an electrode assembly and wound up, thereby improving the quality of the product.

[0005] In order to achieve the above objectives, the present invention adopts the following technical solutions.

[0006] A composite oil-based separator comprising: a substrate membrane; and a moisture-retaining coating applied to at least one side of the substrate membrane, the moisture-retaining coating comprising an inorganic filler, an adhesive polymer, and a moisture-retaining polymer.

[0007] Preferably, the ratio of the weight parts of the adhesive polymer, the moisturizing polymer, and the inorganic filler is 20-90:0.1-1:10-80.

[0008] Preferably, the adhesive polymer is one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride homopolymer, aramid, and fluoropolymer.

[0009] Preferably, the moisturizing polymer is one or more of polyethylene glycol, polypropylene glycol, tripropylene glycol, ethylene glycol, polyvinyl acetate.

[0010] Preferably, the inorganic filler is one or more of aluminum oxide, magnesium hydroxide, aluminum hydroxide, titanium dioxide, silica, boehmite.

[0011] Preferably, the thickness of the moisture-retaining coating is 0.5 μm to 5 μm.

[0012] Preferably, the base film is a PE, PP, PI, aramid, PE / PP / PE composite film, or a ceramic composite separator, and the base film has a melting point of 130°C to 500°C, a thickness of 3 μm to 14 μm, a porosity of 30 to 50%, and an air permeability of 30 sec / 100 cc to 300 sec / 100 cc.

[0013] The second object of the present invention is to provide a method for producing a composite oil-based separator which is easy to operate and has excellent controllability, in view of the shortcomings of the prior art.

[0014] In order to achieve the above objectives, the present invention adopts the following technical solutions.

[0015] Step S1 of dispersing the adhesive polymer in a part of an organic solvent by stirring to obtain an adhesive solution; Step S2: adding a moisturizing polymer to the adhesive solution and dispersing it by stirring to obtain a moisturizing adhesive solution; Step S3 of mixing and dispersing the inorganic filler with the remaining organic solvent to obtain an inorganic filler dispersion; Step S4: mixing and dispersing the moisturizing adhesive solution and the inorganic filler dispersion, and stirring and pulverizing the mixture to obtain a moisturizing slurry; and step S5 of applying the moisture-retaining slurry to at least one surface of the substrate membrane, solidifying to form a moisture-retaining coating, rinsing with water and drying to obtain a composite oil-based separator.

[0016] Preferably, in step S3, 0.01 to 5 parts by weight of a pore-forming agent is further added to the inorganic filler dispersion.

[0017] Preferably, in step S5, the coagulation is performed in a coagulation bath, the temperature of the coagulation bath is 10 to 18°C, the concentration of the solution in the coagulation bath is 10 to 40%, and the solution in the coagulation bath is one or more of NMP, DMAC, acetone, and dimethyl sulfoxide.

[0018] Preferably, in step S5, the washing is performed in a washing tank, the temperature of the washing tank is 20 to 30° C., the concentration of the moisturizing solution in the washing tank is 0.1 to 1%, and the concentration of the organic solvent is 0.01 to 1%.

[0019] A third object of the present invention is to provide a secondary battery which is excellent in antistatic properties, liquid absorption properties and liquid retention properties, in order to overcome the shortcomings of the prior art.

[0020] In order to achieve the above objectives, the present invention adopts the following technical solutions.

[0021] A secondary battery comprising the composite oil-based separator. Effect of the Invention

[0022] Compared with the prior art, the beneficial effects of the present invention are as follows: The composite oil-based separator of the present invention is provided with a moisture-retaining coating, and the moisture-retaining coating is formed by doping and applying a moisture-retaining polymer to the oil-based moisture-retaining coating, so that the moisture-retaining coating has excellent antistatic properties, high liquid absorption / retention properties, high lithium ion conductivity, and high hardness of the electrode assembly, thereby significantly reducing defects when winding the electrode assembly, improving the production efficiency, product yield, and high-rate cycle function of the electrode assembly, and achieving the rapid charging performance of the electrode assembly. [Brief description of the drawings]

[0023] [Figure 1] FIG. 2 is a SEI diagram of the composite oil-based separator of the present invention. [Diagram 2] 1 is a flow chart of the manufacture of the composite oil-based separator of the present invention. [Diagram 3] FIG. 2 is a diagram showing the wettability test results of Example 1 of the composite oil-based separator of the present invention. [Figure 4] FIG. 2 is a diagram showing the wettability test results of Comparative Example 1 of the present invention. [Diagram 5] FIG. 13 is a diagram showing the wettability test results of Comparative Example 2 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] 1. A composite oil-based separator comprising a substrate membrane and a moisture retaining coating applied to at least one side of the substrate membrane, the moisture retaining coating comprising an inorganic filler, an adhesive polymer, and a moisture retaining polymer.

[0025] The composite oil-based separator of the present invention can reduce the static electricity strength of the composite oil-based separator by forming a layer structure having water vapor on the surface of the base film, and can avoid wrinkles when the separator is used in an electrode assembly and wound up. The moisture-retaining coating of the composite oil-based separator of the present invention contains an inorganic filler, which plays a supporting role as a skeleton in the coating and can provide a certain thermal shrinkage resistance, and the inorganic particles have a certain hygroscopicity, so that the static electricity of the separator can be reduced to a certain extent. The moisture-retaining polymer is hydrophilic, so it can absorb moisture and reduce the static electricity strength of the separator. The adhesive polymer firmly adheres the inorganic filler and the moisture-retaining polymer to form a stable structure. The characteristics of the oil-based separator and the above-mentioned moisture-retaining coating reduce the static electricity strength of the separator, and the composite oil-based separator of the present invention can be rapidly charged at a rate of 3C or more.

[0026] Preferably, the ratio of the weight parts of the adhesive polymer, the moisturizing polymer, and the inorganic filler is 20 to 90: 0.01 to 1: 10 to 80. The ratio of the weight parts of the adhesive polymer, the moisturizing polymer, and the inorganic filler is 20: 0.01: 10, 25: 0.01: 10, 30: 0.01: 10, 40: 0.01: 10, 50: 0.01: 10, 60: 0.01: 10, 70: 0.01: 10, 80: 0.01: 10, 90: 0.01: 10, 2 5:0.04:15, 25:0.8:15, 25:0.9:15, 25:0.2:15, 25:0.4:30, 25:0.4:50, 25:0.4:60, 25:0.4:80, 25:0.1:15, 27:1:10, 27:0.7:10, 20:0.1:10, 20:0.1:10. The ratio of weight parts of adhesive polymer, moisturizing polymer, and inorganic filler has a great influence on the properties of the applied moisturizing coating. If the content of adhesive polymer is too high, the moisturizing effect of the moisturizing coating is easily affected, and the antistatic property of the moisturizing coating is further affected. If the content of adhesive polymer is too low, the adhesion strength of the moisturizing coating is easily reduced. The inorganic filler supports the moisture-retaining coating and can impart a certain mechanical strength to the moisture-retaining coating. It can also improve the liquid absorption properties, liquid absorption properties and liquid retention properties of the moisture-retaining coating, and can further improve the antistatic properties of the moisture-retaining coating.

[0027] Preferably, the adhesive polymer is one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride homopolymer, aramid, and fluorine-based polymer. The adhesive polymer has an adhesive effect and can adhere inorganic filler and moisturizing polymer to form a strong reaction product. The melting point of the adhesive polymer is 100°C to 500°C, preferably 100°C, 200°C, 300°C, 400°C, or 500°C.

[0028] Preferably, the moisture-retaining polymer is one or more of polyethylene glycol, polypropylene glycol, tripropylene glycol, ethylene glycol, and polyvinyl acetate. The moisture-retaining polymer has a moisture-retaining effect, improves the moisture-retaining property of the separator, and thereby reduces the static electricity strength of the separator.

[0029] Preferably, the inorganic filler is one or more of aluminum oxide, magnesium hydroxide, aluminum hydroxide, titanium dioxide, silica, and boehmite. The inorganic filler plays a supporting role as a skeleton in the coating, and can provide a certain thermal shrinkage resistance, and the inorganic particles have a certain hygroscopicity, so that the static electricity of the separator can be reduced to a certain extent. The moisture-retaining coating may or may not include an inorganic filler. The effect of the moisture-retaining coating is improved by adding an inorganic filler.

[0030] Preferably, the thickness of the moisture-retaining coating is 0.5 μm to 5 μm. Specifically, the thickness of the moisture-retaining coating is 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, or 5 μm.

[0031] Preferably, the base film is PE, PP, PI, aramid, PE / PP / PE composite film, or ceramic composite film, and the base film has a melting point of 130°C to 500°C, a thickness of 3μm to 14μm, a porosity of 30 to 50%, and an air permeability of 30sec / 100cc to 300sec / 100cc. The base film of the present invention may be a PE film, a PP film, a PI film, an aramid film, a PE / PP / PE composite film, or a ceramic composite film, and the melting point of the base film is 130°C to 500°C, specifically, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 220°C, 240°C, 280°C, 320°C, 340°C, 380°C, 420°C, 460°C, 480°C, or 500°C.

[0032] 2. A method for producing a composite oil-based separator, comprising: Step S1 of dispersing the adhesive polymer in a part of an organic solvent by stirring to obtain an adhesive solution; Step S2: adding a moisturizing polymer to the adhesive solution and dispersing it by stirring to obtain a moisturizing adhesive solution; Step S3 of mixing and dispersing the inorganic filler with the remaining organic solvent to obtain an inorganic filler dispersion; Step S4: mixing and dispersing the moisturizing adhesive solution and the inorganic filler dispersion, and stirring and pulverizing the mixture to obtain a moisturizing slurry; and step S5 of applying the moisturizing slurry to at least one surface of the substrate membrane, solidifying to form a moisturizing coating, rinsing with water and drying to obtain a composite oil-based separator.

[0033] The method for producing the composite oil-based separator of the present invention has a simple and safe process, high applicability of the device, easy operation, excellent controllability, and easy mass production. The composite oil-based separator of the present invention is provided with a moisturizing coating, and the moisturizing coating is formed by doping and applying a moisturizing polymer to the oil-based moisturizing coating, so that the produced moisturizing coating has excellent antistatic properties, high liquid absorption / retention properties, high lithium ion conductivity, and high hardness of the electrode assembly. When the separator is used in the production of a lithium battery, wrinkles are unlikely to occur, production efficiency is high, quality is high, the high-rate cycle function of the electrode assembly is high, and the rapid charging performance of the electrode assembly is achieved. In addition, by controlling the temperature of the solidification bath and the solution blending ratio of the final water washing bath, the antistatic properties, liquid absorption / retention properties, lithium ion conductivity, and hardness of the electrode assembly of the oil-based separator are increased, and the safety and production efficiency of the lithium battery and the high-rate cycle function of the electrode assembly are ensured, and the rapid charging performance of the electrode assembly is achieved. Here, the coating method is any one of dip coating, extrusion coating, gravure coating, and slit coating, and the organic solvent is one or more of NMP, DMAC, acetone, and dimethyl sulfoxide.

[0034] In the present invention, by doping the slurry with a moisture-retaining polymer, the moisture-retaining ability inside the separator is increased, and by introducing a moisture-retaining solution into the water washing tank, an invisible moisture-retaining layer is adsorbed onto the outside of the separator, and the static electricity strength of the separator is significantly reduced (the static electricity strength is the same as that of a water-based coated separator), thereby significantly reducing defects when winding up the electrode assembly.

[0035] In the present invention, by introducing a pore-forming agent, the concentration of the coagulation bath can be controlled while preforming is performed inside the coating, rapid phase separation during phase transformation can be improved, dense pores can be formed on the surface of the coating, rapid transport of lithium ions can be promoted, and the ionic conductivity of the separator can be increased.

[0036] Preferably, in the step S3, 0.01 to 5 parts by weight of a pore-forming agent is further added to the inorganic filler dispersion. The pore-forming mechanism of the pore-forming agent is the principle of phase transformation, that is, when the slurry is immersed in a coagulation bath, the solvent and the non-solvent diffuse into each other through the interface between the liquid membrane and the coagulation bath, and when the exchange of the organic solvent and the non-solvent reaches a certain level, the casting liquid becomes a thermodynamically unstable system, causing phase separation of the casting liquid. After phase separation of the membrane-forming liquid system, the solvent and the non-solvent are further exchanged, and membrane formation occurs due to aggregation of membrane pores, interphase flow, and hardening of the polymer-rich phase. Since the organic solvent and the non-solvent in the coagulation bath are mixed infinitely, the organic solvent and the non-solvent in the coating are exchanged, and when they come into contact with water, a polymer is generated and precipitated, forming a microporous coating structure. The pore-forming agent is one or more of PVP, water, lithium chloride, or glycerol. Preferably, the pore-forming agent is lithium chloride. Some pore-forming agents are water-based liquids, so if they are added directly to the moisturizing adhesive solution, there is a risk of pre-gelation, which will affect the stability and shelf life of the moisturizing adhesive solution, shortening the shelf life from 30 days to 7 days. By mixing the pore-forming agent with the inorganic filler and organic solvent and then adding the moisturizing adhesive solution, the stability of the slurry is ensured, and the shelf life of the moisturizing slurry is up to 30 days.

[0037] Preferably, in step S5, the coagulation is performed in a coagulation bath, the temperature of the coagulation bath is 10-18°C, the concentration of the solution in the coagulation bath is 10-40%, and the solution in the coagulation bath is one or more of NMP, DMAC, acetone, and dimethyl sulfoxide. In the present invention, the moisturizing polymer, the pore former, and the temperature of the coagulation bath act synergistically to eliminate finger-like macropores in the cross section of the coating of the separator, and the pores in the cross section of the coating become dense macropores, thereby increasing the liquid absorption capacity of the separator and ensuring a high liquid retention capacity. The temperature of the coagulation bath is 10°C, 12°C, 14°C, 16°C, and 18°C, and the concentration of the solution in the coagulation bath is 10%, 20%, 30%, and 40%. After applying the moisturizing slurry to the surface of the base film, the base film is passed through a coagulation bath, and the moisturizing slurry is coagulated in the coagulation bath to form a moisturizing coating. The predetermined temperature and the predetermined concentration set for the coagulation bath can provide a better coagulation effect of the moisturizing slurry.

[0038] Preferably, in step S5, the washing is performed in a washing tank, the temperature of the washing tank is 20-30°C, the concentration of the moisturizing solution in the washing tank is 0.1-1%, and the concentration of the organic solvent is 0.01-1%. After solidification, the moisturizing separator is washed in the washing tank to remove the organic solvent remaining in the solidification tank. In addition, since the moisturizing coating absorbs the moisturizing solution in the washing tank, the composite oil-based separator has high antistatic properties, which prevents wrinkles when the composite oil-based separator is wound up, and contributes to improving the quality of the produced electrode assembly.

[0039] 3. A secondary battery comprising the composite oil-based separator according to the present invention. The secondary battery of the present invention is excellent in antistatic properties, liquid absorption properties and liquid retention properties.

[0040] The secondary battery may be a lithium ion battery, a sodium ion battery, a magnesium ion battery, a calcium ion battery, or a potassium ion battery. Preferably, when the secondary battery is a lithium ion battery, the lithium ion battery includes a positive electrode plate, a negative electrode plate, a separator, an electrolyte, and a case, the separator separates the positive electrode plate and the negative electrode plate, and the case houses the positive electrode plate, the negative electrode plate, the separator, and the electrolyte. The separator is the above-mentioned composite oil-based separator. The positive electrode plate includes a positive electrode collector and a positive electrode active material layer provided on at least one surface of the positive electrode collector, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material is represented by the chemical formula Li a Ni x Co y M z O 2-b N b (wherein 0.95≦a≦1.2, x>0, y≧0, z≧0, and x+y+z=1, 0≦b≦1, M is one or more combinations selected from Mn and Al, and N is one or more combinations selected from F, P, and S), but is not limited thereto. The positive electrode active material may include one or more combinations of compounds represented by the formula: LiCoO2, LiNiO2, LiVO2, LiCrO2, LiMn2O4, LiCoMnO4, Li2NiMn3O8, LiNi 0.5 Mn 1.5The positive electrode active material may include one or more of the following combinations: O4, LiCoPO4, LiMnPO4, LiFePO4, LiNiPO4, LiCoFSO4, CuS2, FeS2, MoS2, NiS, TiS2, etc., but is not limited thereto. The positive electrode active material may be modified. The method of modifying the positive electrode active material is known to those skilled in the art, and the positive electrode active material may be modified by, for example, coating or doping, and the material used in the modification may include one or more of the following combinations: Al, B, P, Zr, Si, Ti, Ge, Sn, Mg, Ce, W, etc., but is not limited thereto. On the other hand, the positive electrode current collector is usually a structure or member that collects current, and the positive electrode current collector may be any of various materials suitable in the field as a positive electrode current collector for a lithium ion battery, for example, the positive electrode current collector may include, but is not limited to, a metal foil, etc., and more specifically, may include, but is not limited to, an aluminum foil, etc.

[0041] The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer provided on the surface of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material, which may include, but is not limited to, one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate, or other metals capable of forming an alloy with lithium. Among them, the graphite may be one or more selected from artificial graphite, natural graphite, and modified graphite. The silicon-based material may be one or more selected from elemental silicon, silicon oxygen compounds, silicon carbon composites, and silicon alloys. The tin-based material may be one or more selected from elemental tin, tin oxygen compounds, and tin alloys. The negative electrode current collector is typically a structure or member that collects current, and may be any material suitable in the art as a negative electrode current collector for lithium ion batteries. For example, the negative electrode current collector may include, but is not limited to, a metal foil, and more specifically, may include, but is not limited to, a copper foil.

[0042] The lithium ion battery further includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt, and an additive. Among them, the electrolyte lithium salt may be LiPF6 and / or LiBOB used in a high-temperature electrolyte, at least one of LiBF4, LiBOB, and LiPF6 used in a low-temperature electrolyte, at least one of LiBF4, LiBOB, LiPF6, and LiTFSI used in an electrolyte that prevents overcharging, and at least one of LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. Meanwhile, the organic solvent may be a cyclic carbonate ester including PC and EC, a chain carbonate ester including DFC, DMC, or EMC, and a carboxylate ester including MF, MA, EA, and MP. The additive includes at least one of a film-forming additive, a conductive additive, a flame retardant additive, an overcharge prevention additive, an additive that controls the content of H2O and HF in the electrolyte, an additive that improves low-temperature characteristics, and a multifunctional additive, but is not limited thereto.

[0043] Preferably, the case is made of one of stainless steel and aluminum-plastic film, and more preferably, the case is made of aluminum-plastic film.

[0044] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in more detail with reference to specific embodiments and accompanying drawings, but the embodiments of the present invention are not limited thereto.

[0045] Example 1 Positive electrode plate manufacturing Lithium cobalt oxide, superconducting carbon (Super-P) as a conductive agent, and polyvinylidene fluoride (PVDF) as a binder were uniformly mixed in a mass ratio of 97:1.5:1.5 to prepare a lithium-ion battery positive electrode slurry with a specified viscosity, which was then applied onto an aluminum foil current collector, dried at 85°C, and cold-rolled. After that, trimming, cutting, and slitting were performed, and after slitting, the material was dried under vacuum conditions at 110°C for 4 hours, and a tag was welded to produce a lithium-ion battery positive electrode plate.

[0046] Negative plate manufacturing Graphite, superconducting carbon (Super-P) as a conductive agent, sodium carboxymethylcellulose (CMC) as a thickener, and styrene butadiene rubber (SBR) as a binder were made into a slurry in a mass ratio of 96:2.0:1.0:1.0, which was then applied to a copper foil collector and dried at 85°C. After that, trimming, cutting, and slitting were performed. After slitting, the slurry was dried under vacuum conditions at 110°C for 4 hours, and a tag was welded to produce a lithium-ion battery negative electrode plate.

[0047] Electrolyte production Lithium hexafluorophosphate (LiPF6) was dissolved in a mixed solvent consisting of ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) (the mass ratio of these three was 1:2:1) to obtain an electrolyte solution with a concentration of 1 mol / L.

[0048] Separator manufacturing The manufacturing method of the composite oil-based separator includes the following steps, as shown in Figure 2. Step S1: 3.3 parts of polyvinylidene fluoride and 36.7 parts of polyvinylidene fluoride copolymer were weighed as adhesive polymers and added to 450 parts of NMP, respectively, and stirred and dispersed for 30 minutes at a stirring rotation speed of 30 R and a dispersion rotation speed of 2000 R to obtain an adhesive solution. Step S2: 0.1 parts of polyethylene glycol was added to the adhesive solution, and the mixture was stirred and dispersed for 15 minutes at a stirring rotation speed of 25 R and a dispersion rotation speed of 2000 R, to obtain a moisturizing adhesive solution. Step S3: 60 parts of aluminum oxide as an inorganic filler and 0.1 parts of lithium chloride as a pore-forming agent were weighed out and added to 45 parts of NMP, and the mixture was stirred and dispersed for 30 minutes at a stirring rotation speed of 30 R and a dispersion rotation speed of 2500 R to obtain an inorganic dispersion. Step S4: The moisturizing adhesive solution and the inorganic filler dispersion were mixed, and dispersed at high speed for 30 minutes at a stirring rotation speed of 30 R and a dispersion rotation speed of 2500 R. After stirring uniformly, the mixture was ground for 60 minutes at a grinding rotation speed of 700 rpm, and then filtered to obtain a moisturizing slurry. Step S5: The moisturizing slurry was applied to the two sides of the base film with a thickness of 1.5 μm each, solidified to form a moisturizing coating, washed with water and dried, and a composite oil-based separator with high antistatic properties was obtained, as shown in Figure 1. Here, the ratio by weight of the adhesive polymer, the pore-forming agent, the moisture-retaining polymer, and the inorganic filler was 40:0.1:0.1:60.

[0049] The base film is a 5 μm PE film with a porosity of 40% and an air permeability of 200 sec / 100 cc. The solution in the coagulation tank is a mixture of N-methylpyrrolidone and dimethylacetamide in a mass ratio of 1:1.5. The temperature of the coagulation tank is 15°C, the concentration of the material in the coagulation tank is 30%, the concentration of polypropylene glycol in the final water washing tank is 0.3%, and the temperature of the final water washing tank is 25°C.

[0050] Lithium-ion battery manufacturing The positive electrode plate, antistatic separator, and negative electrode plate were wound up to form an electrode assembly, the antistatic separator was interposed between the positive electrode plate and the negative electrode plate, the positive electrode was pulled out by spot welding an aluminum tag, and the negative electrode was pulled out by spot welding a nickel tag. The electrode assembly was then placed in an aluminum plastic bag, the electrolyte was injected, and a lithium ion battery was manufactured through processes such as sealing, formation, and capacity.

[0051] Example 2 The weight ratio of the adhesive polymer, pore-forming agent, moisturizing polymer, and inorganic filler was 20:1.5:0.5:30, which was different from Example 1, but the rest was the same as Example 1, so a description thereof will be omitted here.

[0052] Example 3 The ratio of the weight parts of the adhesive polymer, pore-forming agent, moisturizing polymer, and inorganic filler was 20:1.8:0.5:30, which was different from Example 1, but the rest was the same as Example 1, so a description thereof will be omitted here.

[0053] Example 4 The ratio of the weight parts of the adhesive polymer, pore-forming agent, moisturizing polymer, and inorganic filler was 20:2:0.5:30, which was different from Example 1, but the rest was the same as Example 1, so a description thereof will be omitted here.

[0054] Example 5 The ratio of the weight parts of the adhesive polymer, pore-forming agent, moisturizing polymer, and inorganic filler was 20:0.2:0.5:30, which was different from Example 1, but the rest was the same as Example 1, so a description thereof will be omitted here.

[0055] Example 6 The weight ratio of the adhesive polymer, pore-forming agent, moisturizing polymer, and inorganic filler was 40:0.2:0.5:30, which was different from Example 1, but the rest was the same as Example 1, so a description thereof will be omitted here.

[0056] Example 7 The weight ratio of the adhesive polymer, pore-forming agent, moisturizing polymer, and inorganic filler was 60:0.2:0.5:30, which was different from Example 1, but the rest was the same as Example 1, so a description thereof will be omitted here.

[0057] Example 8 The weight ratio of the adhesive polymer, pore-forming agent, moisturizing polymer, and inorganic filler was 80:0.2:0.5:30, which is different from Example 1, but the rest was the same as Example 1, so a description thereof will be omitted here.

[0058] Example 9 The weight ratio of the adhesive polymer, pore-forming agent, moisturizing polymer, and inorganic filler was 40:0.2:0.8:30, which was different from Example 1, but the rest was the same as Example 1, so a description thereof will be omitted here.

[0059] Example 10 The ratio of the weight parts of the adhesive polymer, pore-forming agent, moisturizing polymer, and inorganic filler was 20:0.2:0.2:30, which was different from Example 1, but the rest was the same as Example 1, so a description thereof will be omitted here.

[0060] Comparative Example 1 The composite oil-based separator includes a substrate membrane, a ceramic slurry and a water-based polymer slurry applied to the surface of the substrate membrane. A 2 μm ceramic coating is applied to the substrate by a gravure coater with a diagonal roll to obtain a normal ceramic membrane, and then a 0.5 μm polymer coating is applied to both sides of the ceramic membrane by a gravure coater with a diagonal roll, and then dried to obtain a water-based polymer composite membrane.

[0061] Comparative Example 2 The composite oil-based separator includes a laminated support layer and an organic / inorganic particle blend coating layer, and the manufacturing method thereof includes the following steps. Step 1: Using deionized water as a solvent, the water-based adhesive, surfactant, dispersant, thickener, etc. were dissolved at room temperature while stirring at high speed to prepare a solution. Next, polymer particles and inorganic particles were added and stirred at high speed to make a homogenous solution, preparing a water-based slurry. The substances in the slurry were 1.2% by mass of water-soluble polymer thickener, 1.8% by mass of aqueous dispersant, 1.5% by mass of surfactant, 3.5% by mass of water-based adhesive, 32% by mass of polymer particles and inorganic particles, and 60% by mass of deionized water. Step 2: The aqueous slurry prepared in step 1 was applied onto the separator of the support layer by a small-diameter gravure roll coating at a coating speed of 20 m / min. Step 3: The coating film obtained in step 2 was dried in an oven at 60°C to obtain an aqueous separator.

[0062] Here, a small-diameter gravure roll is used for coating, and the coating speed is 40 m / min. The base film for coating is a polypropylene microporous film with a porosity of 42%. A three-stage oven is used for drying, and the oven temperatures of each stage are 50°C, 60°C, and 65°C, respectively. The thickness of the coating layer is 1.5 μm, and the thickness of the film after coating is 19 μm.

[0063] Testing Characteristics The separators produced in the above Examples 1 to 10 and Comparative Examples 1 and 2 were tested for liquid absorption rate, static electricity strength, and puncture strength. The test results are shown in Table 1.

[0064] [Table 1]

[0065] As is clear from Table 1 above, the separator of the present invention had better liquid absorption rate, static electricity strength, and puncture strength than Comparative Example 1 and Comparative Example 2. The separator of the present invention has a good liquid absorption rate, and the liquid absorption rate was as high as 11.2%, because it is provided with a moisturizing coating. In addition, the oil-based separator of the present invention has the same static electricity strength as the aqueous separators in Comparative Examples 1 and 2, that is, the oil-based separator of the present invention has low static electricity strength, so wrinkles are less likely to occur during production and use. From the comparison of Examples 1 to 10, it was found that the performance of the manufactured separator was better when the ratio of the weight parts of the adhesive polymer, the pore-forming agent, the moisturizing polymer, and the inorganic filler was 40:0.1:0.1:60.

[0066] Wettability Test Using a 1 ml syringe, 1 ml of the electrolyte was taken, and one drop of the electrolyte was dropped onto a separator of the same area, and the diffusion area of ​​this drop of electrolyte within 1 minute was observed, and the wettability of the separator with respect to the electrolyte was compared. The test results for Example 1, Comparative Example 1, and Comparative Example 2 are shown in Figures 3 to 5, respectively.

[0067] The characteristics of Example 1, Comparative Example 1, and Comparative Example 2 are compared below, and the comparison results are shown in Table 2.

[0068] [Table 2]

[0069] As is clear from Table 2 above, the separator produced in the present invention had better liquid absorption rate, liquid retention rate, ionic conductivity, and antistatic ability than the separators in Comparative Examples 1 and 2. Specifically, Example 1 had almost the same coating thickness and coating thickness as Comparative Examples 1 and 2, but had a higher coating porosity, higher pin puncture strength, better heat shrinkability, higher dry tack strength, higher bending strength, and higher liquid absorption rate, liquid retention rate, and ionic conductivity. In addition, the oil-based separator of the present application has the same static electricity strength as the water-based separators in Comparative Examples 1 and 2, i.e., has good static electricity strength, is less likely to generate static electricity during use or production, prevents wrinkles, and improves product quality.

[0070] As can be seen from FIG. 3, the separator produced by the present invention has a wettability of about 1 cm2 and a wetted area of ​​about 3.14 cm2. 2 As can be seen from FIG. 4, the separator of Comparative Example 1 has a wetting rate of less than a 1 cm circle and a wetted area of ​​less than 1 cm 2 5, the separator of Comparative Example 2 has a square area with a wettability of more than 0.5 cm and less than 1 cm. From the above, the separator of Example 1 of the present invention has higher wettability and better wetting effect than Comparative Example 1 and Comparative Example 2.

[0071] In addition, those skilled in the art may make changes and modifications to the above embodiments based on the disclosure and teachings of the above specification. Therefore, the present invention is not limited to the above specific embodiments, and any obvious improvements, substitutions or modifications made by those skilled in the art based on the present invention are within the scope of protection of the present invention. In addition, although specific terms are used in this specification, these terms are for the convenience of explanation and do not limit the present invention.

Claims

1. A composite oil-based separator comprising: a substrate film; and a moisture-retaining coating applied to at least one surface of the substrate film, the moisture-retaining coating comprising an inorganic filler, an adhesive polymer, and a moisture-retaining polymer.

2. The composite oil-based separator according to claim 1, characterized in that the weight ratio of the adhesive polymer, the moisture-retaining polymer, and the inorganic filler is 20-90:0.01-1:10-80.

3. The composite oil-based separator according to claim 1 or 2, characterized in that the adhesive polymer is one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride homopolymer, aramid, and fluorine-based polymer.

4. 3. The composite oil-based separator according to claim 1, wherein the moisture-retaining polymer is one or more of polyethylene glycol, polypropylene glycol, tripropylene glycol, ethylene glycol, and polyvinyl acetate.

5. 3. The composite oil-based separator according to claim 1 or 2, characterized in that the inorganic filler is one or more of aluminum oxide, magnesium hydroxide, aluminum hydroxide, titanium dioxide, silica, and boehmite.

6. The composite oil-based separator according to claim 1, wherein the thickness of the moisture-retaining coating is 0.5 μm to 5 μm.

7. The composite oil-based separator according to claim 1 or 6, characterized in that the base film is PE, PP, PI, aramid, PE / PP / PE composite film, or ceramic composite separator, and the base film has a melting point of 130°C to 500°C, a thickness of 3μm to 14μm, a porosity of 30 to 50%, and an air permeability of 30sec / 100cc to 300sec / 100cc.

8. Step S1: Stirring and dispersing the adhesive polymer in a portion of an organic solvent to obtain an adhesive solution; Step S2: adding a moisturizing polymer to the adhesive solution and dispersing it by stirring to obtain a moisturizing adhesive solution; Step S3 of mixing and dispersing the inorganic filler with the remaining organic solvent to obtain an inorganic filler dispersion; Step S4: mixing and dispersing the moisturizing adhesive solution and the inorganic filler dispersion, and stirring and pulverizing the mixture to obtain a moisturizing slurry; and step S5 of applying the moisture-retaining slurry to at least one surface of the substrate membrane, solidifying the slurry to form a moisture-retaining coating, rinsing the slurry with water and drying the slurry to obtain a composite oil-based separator.

9. The method for manufacturing a composite oil-based separator according to claim 8, characterized in that in the step S3, 0.01 to 5 parts by weight of a pore-forming agent is further added to the inorganic filler dispersion.

10. In the step S5, the solidification is performed in a solidification bath, the temperature of the solidification bath is 10 to 18°C, the concentration of the solution in the solidification bath is 10 to 40%, and the solution in the solidification bath is one or more of NMP, DMAC, acetone, and dimethyl sulfoxide. The method for producing a composite oil-based separator according to claim 9.

11. The manufacturing method of the composite oil-based separator according to claim 10, characterized in that in step S5, the washing is performed in a washing tank, the temperature of the washing tank is 20-30°C, the concentration of the moisturizing solution in the washing tank is 0.1-1%, and the concentration of the organic solvent is 0.01-1%.

12. A secondary battery comprising the composite oil-based separator according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Organic-inorganic composite electrolyte membrane, preparation method and application thereof

    CN104505484A

  • Metal-ceramic microsphere, diaphragm containing metal-ceramic microsphere and lithium ion battery containing diaphragm

    CN112615110A

  • Lithium ion battery isolating membrane

    CN112652861A

  • Coating slurry for manufacturing separator, separator for electrochemical device and manufacturing method thereof

    JP2021520607A